Young Pupils' Joint Creation of Multimodal Fairy Tales Using Analogue and Digital Resources - Marina Wernholm; Kristina Danielsson; Andreas Ebbelind; Hanna Palmér; Emelie Patron (MDPI AG, 2023)
The present study aimed to explore 'what's happening' and 'what's possible', when young pupils jointly create multimodal texts in small groups. This was achieved by studying the process when pupils in a grade 2 classroom (i) created handwritten fairy tales, (ii) drew images, and then, (iii) transformed them into animated multimodal texts using a digital application during three small-group activities. Data comprises video recordings, pupils' multimodal texts (writing and drawings), teaching materials, and lesson plans. This qualitative case study focuses on one group of three pupils aged 8-9. The study is theoretically grounded in the designs for learning perspective, with the Learning Design Sequence Model utilized as an analytical tool. The teacher's design for learning-including her planned activities and the resources made available to the pupils-appeared to have a major impact on what happens and what becomes possible for the pupils in their design for learning. The teacher's design also influenced what competencies the pupils could (and chose) to draw upon in the different activities. An important result was that the pupils positioned themselves and each other in quite different ways during the small-group activities, which partly could be explained by the different affordances of the resources provided, as well as the teacher's design. The detailed descriptions of how the pupils' positioning changed in relation to the teacher's design for learning and the available resources add valuable knowledge to the field of educational research.